2007
DOI: 10.1016/j.cellbi.2006.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mid‐late mouse fetus' microenvironment on the growth of tumor cells after intrauterine transplantation

Abstract: Successful intrauterine transplantation (IUT) of stem cells for treatment of fetal defects in some animal models of human diseases has prompted us to study the mechanisms of transplantation, immunological tolerance and embryonic environment. The objective of this study was to determine whether intrauterine transplantation of tumor cells would affect the survival and growth of the tumor cells themselves as well as fetus development. A total of 2 x 10(6) H(22) cells or S(180) cells were transplanted into the amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Hendrix and colleagues performed multiple studies demonstrating that embryonic microenvironments prevent human melanoma cells from tumorigenesis after implantation into the embryo of zebrafish [150] or revert the metastatic melanoma phenotype to its cell type of origin in an embryonic chick model [24]. The capability of the embryonic microenvironment to inhibit tumorigenesis and reprogram metastatic cancer cells to a less aggressive phenotype was confirmed using an in vitro mouse embryo model [151] and intrauterine transplantation mouse model [152], respectively. These studies reveal the uniqueness of the embryonic microenvironment in halting tumorigenicity.…”
Section: Embryonic Microenvironment and Cancermentioning
confidence: 99%
“…Hendrix and colleagues performed multiple studies demonstrating that embryonic microenvironments prevent human melanoma cells from tumorigenesis after implantation into the embryo of zebrafish [150] or revert the metastatic melanoma phenotype to its cell type of origin in an embryonic chick model [24]. The capability of the embryonic microenvironment to inhibit tumorigenesis and reprogram metastatic cancer cells to a less aggressive phenotype was confirmed using an in vitro mouse embryo model [151] and intrauterine transplantation mouse model [152], respectively. These studies reveal the uniqueness of the embryonic microenvironment in halting tumorigenicity.…”
Section: Embryonic Microenvironment and Cancermentioning
confidence: 99%
“…Several studies have revealed that the embryonic microenvironment can reverse the malignant phenotype of cancer cells. In fact, the ability of embryonic models to reconvert malignant cells to a normal phenotype has been demonstrated in chick, mouse, and zebrafish embryos (12)(13)(14)(15). Tumor cells and embryonic stem cells (ESCs) have similar biological characteristics, such as high selfrenewal, infinite proliferation, and signal transduction (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the anti-angiogenic effect and the anti-tumor activity of pcDNA-tum-5 on mice bearing S180 sarcoma tumor (Ma et al 2007). The results showed that pcDNA-tum-5 has an inhibition effect on the formation of vessels and tumor growth.…”
Section: Introductionmentioning
confidence: 99%